Women and gender in early modern Europe - Wiesner, Merry E. (Cambridge : Cambridge University Press, 1993)
This is a major new textbook, designed for students in all disciplines seeking an introduction to the very latest research on all aspects of women's lives in Europe from 1500 to 1750, and on the development of the notions of masculinity and femininity. The coverage is geographically broad, ranging from Spain to Scandinavia, and from Russia to Ireland, and the topics investigated include the female life-cycle, literacy, women's economic role, sexuality, artistic creations, female piety - and witchcraft - and the relationship between gender and power. To aid students each chapter contains extensive notes on further reading (but few footnotes), and the approach throughout is designed to render the subject in as accessible and stimulating manner as possible. Women and Gender in Early Modern Europe is suitable for usage on numerous courses in women's history, early modern European history, and comparative history.
Lisäpainokset: Repr. 1995. - 1996.
Keywords: Women. -- History. -- Europe; naisen asema -- Eurooppa -- 1500-1750; naishistoria -- Eurooppa -- 1500-1750; naiset -- kulttuuri -- Eurooppa -- 1500-1750; naiset -- elämänkaari -- Eurooppa -- 1500-1750; elämänkaari -- naiset -- Eurooppa -- 1500-1750; naiseus -- käsitykset; naistutkimus -- sosioekonominen asema; sukupuolitutkimus -- valta